ANALISIS DETERMINAN PENDAPATAN PEDAGANG KAKI LIMA DI KAWASAN MALIOBORO PASCA RELOKASI - Fathurrahman, Ayif; Arsianto, Anisa Nendiya (LPPM Universitas Multi Data Palembang, 2025)
The Yogyakata Special Region Government has made a policy regarding regulations for the Malioboro area, namely regarding Relocation in order to regulate the Malioboro area into an area that is clean from street vendors. This study uses independent variables, namely business capital, length of business, location, working hours, and level of education, while the independent variable uses income. This study aims to determine the business capital, length of business, location, working hours, and level of education on the terraces of Malioboro have an influence on income and to determine the income of post-relocation street vendors. In this study, researchers used primary data and took samples using a questionnaire.The researchers only took 100 respondents after going through the Sloving formula calculation method, fromthe total population of street vendors on the terraces of Malioboro. The analytical tool method used by the researcher is multiple linear regression which as the dependent variable is income and the independent variables are business capital, length of business, location, working hours, and level of education.